Contrasting seasonality of 137Cs concentrations in two stream animals that share a trophic niche. (15th December 2022) - Sakai, Masaru; Ishii, Yumiko; Tsuji, Hideki; Tanaka, Asuka; Jo, Jaeick; Negishi, Junjiro N.; Hayashi, Seiji
Abstract: Understanding the seasonality of 137 Cs concentrations in aquatic animals is crucial for reviving local inland fisheries. The seasonality of 137 Cs concentrations in animals is expected to vary, even if focal species consume similarly contaminated foods because the 137 Cs excretion rate is species-specific, and 137 Cs uptake by foraging autochthonous food resources also vary among seasons. Here, we conducted a seasonal monitoring survey of dissolved 137 Cs concentrations as an indicator of the contamination level of food resources and measured 137 Cs concentrations in two carnivorous aquatic animals ( Palaemon paucidens and Rhinogobius sp.) that share a trophic niche in a stream connected to a dam reservoir. The dissolved 137 Cs concentration had clear seasonality—high in summer and low in winter. The 137 Cs concentrations in the animals revealed a different seasonal pattern—it peaked in October in P. paucidens and peaked in February in Rhinogobius . Overall, the 137 Cs concentration was relatively higher in P. paucidens than in Rhinogobius, suggesting that P. paucidens has a lower excretion rate than Rhinogobius . Consequently, the seasonality of the 137 Cs concentration in P. paucidens showed temporal changes similar to those of the dissolved 137 Cs concentration, which were likely affected by 137 Cs uptake through foraging, whereas that in Rhinogobius was controlled by 137 Cs excretion. This study shows that the seasonality of 137 Cs concentration can differ between sympatric animals that share a trophic niche. Accumulating knowledge and comparing the seasonality of 137 Cs concentrations in fisheries species based on the balance between uptake and excretion will be valuable to determine the appropriate seasons to obtain less-contaminated products. Graphical abstract: Image 1 Highlights: Two sympatric species that belong to different phyla was compared. Stable carbon and nitrogen ratios showed that the two species share a trophic niche. Dissolved 137 Cs concentration peaked in summer and dropped in winter. The two species showed different seasonality of 137 Cs concentrations. 137 Cs seasonality varies with interspecific variations of excretion rates in animals.